2021
DOI: 10.1155/2021/2879392
|View full text |Cite
|
Sign up to set email alerts
|

Construction and Application Analysis of Carbon Emission Influence Factor Model of Energy Consumption in Mining Industry

Abstract: With the proposal of China’s “double carbon goal,” as a high energy-consuming industry, it is urgent for the mining industry to adopt a low-carbon development strategy. Therefore, in order to better provide reasonable suggestions and references for the low-carbon development of mining industry, referring to the methods and parameters of the 2006 IPCC National Greenhouse Gas Inventory Guidelines and China’s Provincial Greenhouse Gas Inventory Preparation Guidelines (Trial), a carbon emission estimation model is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…e calculation process of carbon emission of energy consumption in mining industry and its subdivisions refers to the research of Wei et al [26], and the specific calculation results are shown in Table 7.…”
Section: Analysis Of Calculation Results Of Carbon Emission Of Energy...mentioning
confidence: 99%
See 1 more Smart Citation
“…e calculation process of carbon emission of energy consumption in mining industry and its subdivisions refers to the research of Wei et al [26], and the specific calculation results are shown in Table 7.…”
Section: Analysis Of Calculation Results Of Carbon Emission Of Energy...mentioning
confidence: 99%
“…e five subsectors are abbreviated as coal sector, petroleum and natural gas sector, ferrous metal sector, nonferrous metal sector, and nonmetal sector. For the calculation method and process of carbon emissions of mining industry and subindustries involved in this study, Wei's et al's research is referred [26].…”
Section: Data Processingmentioning
confidence: 99%
“…The carbon emissions related to trucking work and were calculated by considering the carbon emission factors of the road and the distance as determined by the best-route analysis based on GIS. Lili Wei et al (2021) [13] established a carbon emission estimation model to estimate the carbon emissions of the energy consumption of China's mining industry from 2000 to 2020, referring to the methods and parameters of the 2006 IPCC National Greenhouse Gas Inventory Guidelines. Then, using the extended Kaya identity and the LMDI model, analyzed the influencing factors of carbon emissions in the mining industry, including energy carbon emission intensity, energy structure, energy intensity, industrial structure, and output value.…”
Section: Introductionmentioning
confidence: 99%